sistem operasi mobile Komparasi Struktur Sistem Operasi Mobile Dampak Pengelolaan Memori dan Performa Aplikasi - Sukmana Wibowo, Mohamad Hegar; Al Ayubi, Muhammad Din; Rilvani, Elkin (Politeknik Negeri FakFak, 2024)
Mobile operating systems are software designed to manage the fundamental functions of devices. The most dominant mobile operating systems in today's market are Android and iOS, each capturing their respective user segments with distinct approaches. iOS is a mobile operating system developed by Apple, tailored for its smartphones, while Android is designed by the Open Handset Alliance (led primarily by Google) and developed for Android smartphones and tablets. This study employs a comparative method to analyze the performance and memory management of Android 11 and iOS 14. The findings reveal that iOS 14 is more efficient, with an average memory allocation time of 90 ms, compared to Android 11’s 120 ms. Android 11 offers greater flexibility in handling heavy applications but at the cost of higher memory consumption. Conversely, iOS 14 demonstrates superior efficiency and stability in memory usage, particularly for lightweight and medium applications.